KEDUDUKAN MAJELIS KEHORMATAN DISIPLIN KEDOKTERAN INDONESIA (MKDKI) DAN KONSIL KEDOKTERAN INDONESIA (KKI) DALAM PENEGAKAN DISIPLIN KEDOKTERAN DI INDONESIA (Studi Putusan Mahkamah Agung RI Nomor: 298K/TUN/2012) - Andryawan . (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2016)
Health is one of human rights and the constitutional rights of every citizen of Indonesia. Government as manager of the Republic of Indonesia, are obligated to protect and guarantee the right to health care for all citizens without exception. One of them through the provision of services of the ministry of health by doctors. As a key element in the administration of medical practice, so the importance of the role of doctors and often leads to the assumption that the doctor is a "God" who never made a mistake / violations in the medical act. With the enactment of Law No. 29 of 2004, then began organizing medical practice into a new era. This was followed by the establishment of the Indonesian Medical Displinery Board (IMDB) and the Indonesian Medical Council (INAMC) as a body / supervisory institution organizing medical practice in Indonesia. But so far, the position of both institutions still raises problems of law. One of them in terms of discipline by IMDB often become unproductive because of constraints of the INAMC. Even sometimes discipline conducted by IMDB even canceled by the State Administrative Court. This led to the discipline of medicine be hung without any certainty. When it was clearly stated that the enforcement of medical discipline committed by IMDB shall be final and binding on the parties. But the facts show that IMDB powerless to enforce the medical discipline of his mandate.